Between Innovation and Prohibition: A Contextualised Islamic Legal Analysis of Cryptocurrency Compliance with Sharīʿah Principles in the Indonesian Context - Sahban Sahban; Zainuddin Zainuddin; Wahida Wahida (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
Despite growing scholarly attention to Islamic finance and digital technology, the existing literature has not produced a systematic contextualised Islamic legal analysis that integrates classical fiqh doctrines — particularly gharār, maysīr, and ribā — with the structural and functional characteristics of contemporary cryptocurrency instruments. This lacuna generates normative uncertainty for Muslim investors, Islamic financial institutions, and Sharīʿah regulatory authorities in Indonesia. This study critically examines the extent to which cryptocurrency — as a blockchain-based financial technology — satisfies or violates Sharīʿah principles, and proposes a contextualised Islamic legal framework for evaluating cryptocurrency compliance within the Indonesian regulatory and fatwa environment. A normative legal research design was employed, combining a conceptual approach (analysis of classical fiqh categories and maqāṣid al-Sharīʿah) with a statutory approach (examination of DSN-MUI Fatwa No. 116/2017, OJK Regulation No. 27/2024, and Bappebti regulatory instruments). Primary and secondary legal sources were analysed using qualitative descriptive method with purposive thematic synthesis. Standard cryptocurrencies such as Bitcoin exhibit characteristics of gharār fāhish (excessive uncertainty) and maysīr due to extreme price volatility and speculative trading structures, rendering them presumptively impermissible under the majority scholarly position. Ribā-related concerns emerge specifically in crypto lending and DeFi yield mechanisms. However, the underlying blockchain technology demonstrates structural alignment with Sharīʿah principles of amānah (trustworthiness) and transparency. Asset-backed, Sharīʿah-screened tokens present a viable pathway toward compliance. This study offers the first contextualised Islamic legal framework that disaggregates cryptocurrency compliance analysis by instrument type, distinguishing standard cryptocurrencies, asset-backed stablecoins, and blockchain infrastructure — an analytical move absent in prior literature. Unlike existing studies that assess cryptocurrency compliance wholesale, this paper applies maqāṣid al-Sharīʿah's hifz al-māl (protection of wealth) as an evaluative metric, demonstrating that partial compliance is possible under specific structural conditions. The findings provide actionable guidance for Indonesian Sharīʿah authorities and policymakers navigating the regulatory transition from Bappebti to OJK.